2020
DOI: 10.1016/j.jcte.2020.100234
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obstructive sleep apnea risk and associated factors among patients with type 2 diabetes mellitus on follow up at Jimma Medical Center, Southwest Ethiopia

Abstract: Highlights Obstructive sleep apnea is a periodic, partial or complete obstruction in the upper airway during sleep. It is highly prevalent among obese patients with type two diabetes mellitus. There were high numbers of participants with high risk of OSA among the study participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 32 publications
5
10
4
Order By: Relevance
“…It is similar to different studies that BMI, snoring and smoking are significant risk factors (Cho et al, 2020;Foroughi et al, 2017). In contrast, our study did not reveal that gender, observed apnea, blood pressure, and neck size are significantly associated with risk of OSA (Abdissa, 2020;Wong et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…It is similar to different studies that BMI, snoring and smoking are significant risk factors (Cho et al, 2020;Foroughi et al, 2017). In contrast, our study did not reveal that gender, observed apnea, blood pressure, and neck size are significantly associated with risk of OSA (Abdissa, 2020;Wong et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence of high-risk OSA among T2DM patients was 42.2%. This result was in line with the studies conducted in Ethiopia (45.5%) [ 40 ], Kenya (44.4%) [ 41 ], Saudi Arabia (44.3%) [ 39 ], and Jordan (48.5%) [ 38 ]. This resemblance could be due to similarity in the population studied as well as study tools and procedures: Kenya, Saudi Arabia, and Jordan used the Berlin questionnaire to diagnose high-risk OSA which was similar to the current study.…”
Section: Discussionsupporting
confidence: 91%
“…The study also identified factors: age, neck grasp, waist circumference, and the presence of T2DM-related complications were independent predictors of high-risk OSA among T2DM patients. Although neck circumference was a common independent predictor of high-risk OSA in prior studies [ 37 40 ], this study couldn’t find an independent association. The reason could be the gender and size normative neck gap measure might predict better and veneer the predicting ability of neck circumference, which are two parameters that measure the neck mass independently, to predict high-risk OSA.…”
Section: Discussioncontrasting
confidence: 68%
“…Due to the limitation of sleep labs in hospitals and taking into account the intricacy of the above diagnostic technique, the procedure is quite expensive and cumbersome to use. A minimum of 22 lead wires are connected to the patient's body to acquire 12 different PSG signals, which makes the signal analysis part quite tricky and also cause discomfort to the patient [ 4 , 5 ]. Apnea-Hypopnea Index (AHI) is used to analyze the severity of the disease, which is measured as the number of apneic episodes in the PSG recordings per hour of sleep, in comparison with the American Academy of Sleep Medicine (AASM).…”
Section: Clinical Backgroundmentioning
confidence: 99%